Management of a pediatric patient with ataxia telangiectasia: Report of a rare case in which diagnostic radiographs are contraindicated - Mebin George Mathew (Journal of Family Medicine and Primary Care, 2020)
Ataxia telangiectasia is a rare neurodegenerative autosomal recessive multisystem disorder which has been reported only once in the dental literature. It is characterized by cerebellar degeneration, telangiectasia, immunodeficiency, and cancer susceptibility and radiation sensitivity. Till date, this disorder remains the only condition in dentistry in which diagnostic radiographs are not allowed. The present case report is aimed to discuss the management of ataxia telangiectasia in a pediatric patient.